A methodological review of preference displacement research. (23rd November 2020) - White, Allison N.; Melanson, Isaac J.; Sipila‐Thomas, Emma S.; Brodhead, Matthew T.
Abstract: The purpose of this review was to identify and compare methodological components of preference displacement research and outcomes. We coded, categorized, and defined patterns of preference displacement for a total of 133 participants across 10 studies. We found that patterns of displacement differed within and across studies, and over 46% of participants did not engage in patterns of displacement. Therefore, the commonly held notion that edible stimuli are more likely to displace tangible stimuli is not as ubiquitous as once thought. However, due to considerable variation in methodology and reporting across reviewed studies, it is difficult to determine what variables may be responsible for obtained study outcomes. We conclude that future researchers consider the importance of each methodological variable coded in our review, and make methodological decisions in the context of the research question they are looking to answer. We also provide additional suggestions for future research and clinical practice.